Abdominal Cocoon Syndrome in a Liver Transplant Patient: A Case Report and Review of the Literature - Mckey, Remy; Charara, Rim; El Sayed, Mohamad Hussein; Bahr, Abbas (International Journal of Clinical Research, 2023)
Introduction: Cocoon syndrome is an uncommon cause of intestinal obstruction caused by the formation of a fibrous band around small intestines, thought to be caused by chronic peritoneal inflammation and associated with several conditions such as liver cirrhosis and liver transplantation. Case Report: We present a case of a 72-year-old male patient who had liver transplantation three years ago for liver cirrhosis. He had an acute presentation of intestinal obstruction where a computed tomography (CT) scan showed dilated bowel loops and signs of intestinal ischemia, which warranted surgical laparotomy where the diagnosis of cocoon syndrome (sclerosing encapsulating peritonitis) was made and was then treated by adhesiolysis. No immediate or postoperative complications were documented and his life was back to normal. Conclusion: Therefore, an abdominal cocoon is a challenging diagnosis and should be considered in front of intestinal obstruction, especially in those with risk factors such as liver transplantation.